The Impact Of Standard Operating Procedures, Motivation, And Transformational Leadership On Teacher Performance Through Organizational Culture: Study In Junior High Schools In Kodi Bangedo District, Southwest Sumba Regency, NTT - Radu, Yosef Yingo; Uripan, Koen Irianto; Soleha, Siti Nur; Endriatmoko, Yosa; Suminar, Lintang (Abadi Institute, 2025)
This study aims to analyze the influence of Standard Operating Procedures (SOP), work motivation, and transformational leadership on teacher performance with organizational culture as a mediating variable in junior high schools in Kodi Bangedo District, Southwest Sumba Regency, NTT. All 155 teachers were sampled through census techniques. The analysis uses Partial Least Square (PLS) based on Structural Equation Modeling (SEM). The results of the study show that SOPs, work motivation, and transformational leadership have a positive effect on teacher performance. Consistent SOPs improve work efficiency, motivation encourages commitment and creativity, and transformational leadership inspires teachers to work. Organizational culture has also been proven to mediate the influence of these three variables, where a positive culture strengthens teacher performance optimally. This finding emphasizes the importance of synergy between SOPs, motivation, leadership, and organizational culture in improving the quality of education in junior high schools in Kodi Bangedo District.